Developing communicative competence of primary school pupils through interactive methods (Journal of Science-Innovative Research in Uzbekistan, 2025)
The development of communicative competence in primary school pupils is a critical component of modern education, especially in a world where effective communication is essential for academic, social, and personal success. This article explores the theoretical foundations, practical strategies, and classroom applications for fostering communicative competence among young learners. Beginning with an analysis of its definition and importance, the study highlights the cognitive, social, and linguistic benefits of nurturing communication skills from an early age. The research then focuses on interactive teaching methods—including role-plays, group discussions, cooperative learning, and digital tools—as effective means of enhancing learners’ linguistic and social interaction abilities. Drawing on key theories such as Sociocultural Theory (Vygotsky), Communicative Language Teaching, and Cooperative Learning Theory, the paper demonstrates how these approaches support language development in real-life contexts.